Underwater laser cutting of thick stainless steel blocks using single and dual nozzles. (April 2021) - Oh, Seong Y.; Shin, Jae Sung; Park, Seungkyu; Kim, Taek Soo; Park, Hyunmin; Lee, Lim; Lee, Jonghwan
Highlights: Laser cutting was performed using fiber laser with two nozzle configurations. The 1st nozzle configuration involved a single minimum length nozzle (MLN). The 2nd configuration consisted of a truncated aerospike nozzle coupled with an MLN. The dual nozzles increase the permissible thickness of the steel blocks being cut. This is a convenient approach in underwater laser cutting technology. Abstract: Laser cutting was performed using a 6-kW fiber laser with two different nozzle configurations to extend the permissible cutting thickness of steel blocks in a water environment. The first nozzle configuration involved a single minimum length nozzle (MLN) operating at an upstream gas gauge pressure of 15 bar; the second configuration consisted of a truncated aerospike nozzle coupled with an MLN. These configurations were designed to form a core air-filled cavity with the submerged jet to have denser and more lengthened characteristics for extending the possible transmission distance of the high-power laser beam, which is vulnerable to water absorption. Before underwater cutting, we performed a Schlieren visualization measurement of the gas jet's flow behavior as it was discharged from the single and dual nozzles in the ambient air, after which, the stainless steel blocks were laser-cut underwater using both nozzle configurations. The thickness of the selected steel blocks varied from 60 to 80 mm according to the capabilities of the nozzles used to form the air cavity.